FEM analysis of a new miniplate: stress distribution on the plate, screws and the bone - Nalbantgil, Didem; Tozlu, Murat; Ozdemir, Fulya; Oztoprak, Mehmet Oguz; Arun, Tulin (European Journal of Dentistry, 2012)
Objectives: Non-homogeneous force distribution along the miniplates and the screws is an unsolved question for skeletal anchorage in orthodontics. To overcome this issue, a miniplate structure was designed featuring spikes placed on the surface facing the cortical bone. The aim of this study was to examine and compare the force distribution of the newly designed plate-screw systems with the conventional one.Methods: A model of bone surface with 1.5 mm cortical thickness, along with the two newly designed miniplates and a standard miniplate-screw were simulated on the three-dimensional model. 200 g experimental force was applied to the tip of the miniplates and the consequential effects on the screws and cortical bone was evaluated using three-dimensional finite element method.Results: As a result of this finite element study, remarkably lower stresses were observed on the screws and the cortical bone around the screws with the newly designed miniplate when compared with the conventional one.Conclusion: The newly designed miniplate that has spikes was found effective in reducing the stress on and around the screws and the force was distributed more equivalently. (Eur J Dent 2012;6:9-15)
Keywords: Miniplate; stability; stress distribution; finite element analysis